Endophytic microorganisms for the preservation of vegetables (Research, Society and Development, 2022)
The loss of fruit and vegetable food caused by post-harvest diseases is a major problem in the world. Inside the plant, several phenomena related to microbial endophyte activities occur, starting from the direct stimulation of the plant's growth by the action of phytohormones or by the production of metabolites as a defense mechanism in the plant. Knowing the microbial community helps in managing the prevention of physiological disorders and post-harvest diseases. By reviewing the literature, the mechanisms of biocontrol of microorganisms, the action of most common pathogens, the genera of microorganisms of commercial interest, and the prospect of endophytic microorganisms for the future in the fruit and vegetable postharvest were observed. It is concluded that the global demand for healthier foods is on the rise, as disease control through endophytic microorganisms is a reality in the post-harvest period and is a challenge for future research to obtain greater ecological benefits.